2012
DOI: 10.1002/hyp.9304
|View full text |Cite
|
Sign up to set email alerts
|

Controls of streamflow generation in small catchments across the snow–rain transition in the Southern Sierra Nevada, California

Abstract: Processes controlling streamflow generation were determined using geochemical tracers for water years 2004–2007 at eight headwater catchments at the Kings River Experimental Watersheds in southern Sierra Nevada. Four catchments are snow‐dominated, and four receive a mix of rain and snow. Results of diagnostic tools of mixing models indicate that Ca2+, Mg2+, K+ and Cl− behaved conservatively in the streamflow at all catchments, reflecting mixing of three endmembers. Using endmember mixing analysis, the endmembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 39 publications
(90 reference statements)
8
54
0
1
Order By: Relevance
“…If precipitation at the nearby sites did not accompany a snow-depth increase at the study sites, that precipitation was assumed to be rain. Snow-density data from nearby US Bureau of Reclamation snow-pillow sites were used to compute snow water equivalent (SWE) for the stream and meteorological station locations according to the method outlined in Liu et al [26]. The Blue Canyon station was used for the northern site and a combination of the Chilkoot Meadow and Poison Ridge stations for the southern site.…”
Section: Discussionmentioning
confidence: 99%
“…If precipitation at the nearby sites did not accompany a snow-depth increase at the study sites, that precipitation was assumed to be rain. Snow-density data from nearby US Bureau of Reclamation snow-pillow sites were used to compute snow water equivalent (SWE) for the stream and meteorological station locations according to the method outlined in Liu et al [26]. The Blue Canyon station was used for the northern site and a combination of the Chilkoot Meadow and Poison Ridge stations for the southern site.…”
Section: Discussionmentioning
confidence: 99%
“…NSE and LNSE for B201 are more sensitive to DEM resolution compared to the other watersheds. Other research [33] suggested that B201 has a smaller subsurface flow component than other Bull sites, and the authors hypothesized that the bedrock geomorphology at B201 may be different from the other watersheds. These results suggest that the model accuracy of streamflow depends on how well surface topography at different resolutions emulates the subsurface topography for individual watersheds.…”
Section: Sensitivity Of Estimated Ecohydrologic Variables To Dem Resomentioning
confidence: 99%
“…Conditions at the soil/bedrock or saprolite/bedrock contact may be influential in determining storage capacity. 25 Permeable bedrock, or the depth of weathered bedrock or saprolite may constitute the primary reservoir of storage for baseflow generation (Liu et al 2013, Price 2011, Rempe and Dietrich 2014, Salve et al 2012, Sayama et al 2011. While soil depths are typically assumed to be greater on lower gradient slopes and in valley fill (Price 2011), studies of the depth of the hydrologically active weathered bedrock zones in argillite and granite have found increasing depth with higher slope position (Holbrook et al 2014, Rempe and Dietrich 2014, Salve et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Water that contributes to baseflow may move 5 through larger pores and preferential flow pathways deep into the saprolite, out of the reach of vegetation except where regolith depths are relatively shallow (Liu et al 2013, Salve et al 2012. Transpiration by riparian vegetation may be less limited by water availability and thus have a pronounced effect on baseflows (Bernal and Sabater 2012, Bren 1997, Hicks et al 1991, Moore et al 2011, Reid 2012, Richard et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation